The European Seismic Risk Model 2020 (ESRM20) - Helen Crowley (2019)
This study describes the development of the various components of the European Seismic Risk Model 2020 (ESRM2020) which will be able to generate, using open-source software developed by the GEM Foundation (the Open Quake-engine), a number of Europe-wide risk metrics including average annualised human and economic losses (AAL), probable maximum losses (PML), and risk maps showing the losses for specific return periods or scenario events. The latest developments towards pan-European exposure models for residential and non-residential buildings and fragility/vulnerability models for damage, economic loss and casualty assessment will be presented. For engineered buildings within the exposure model (reinforced concrete, steel), a simulated design is undertaken using the key aspects of seismic design codes in force across Europe over the past 100 years. The designed MDOF building is then transformed to a SDOF model and nonlinear dynamic analyses are run using a large number of ground motion records, after which cloud analysis is used to develop the fragility functions. For non-engineered buildings (unreinforced masonry, confined masonry, adobe), the SDOF models have been directly developed from simplified formulae, experimental tests and previous studies. Collaboration from local experts at various stages of the model development, initiated through workshops, is an important component of the model, as well as the extensive calibration and validation.